Tindakan Komunikatif Masyarakat “Kampung Preman” dalam Proses Pemberdayaan - Yuli Setyowati (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2016)
This study aims to identify and analyze the process of community empowerment at “Badran thugs village” in Yogyakarta through PT. Sarihusada CSR program and to analyze communicative action of “Badran thugs village” in the empowerment process. This study is qualitative in nature using case study design. Data were collected by in-depth interviews, observation, and documentation. Data were analyzed using interactive model. This research concludes that (1) the people in Badran have lived with the stigma of “thugs village” characterized by poor condition of social and economic. Socially, people in Badran are less educated. Economically, people were unable to pay credit to moneylenders. The process of empowerment in Badran was initited by community leaders by taking various efforts, such as forming group activities in order to release people from the bondage of moneylenders, establishing Pusat Kegiatan Belajar Masyarakat (Community Learning Center) and early childhood program, and also to improve family health and environment. PT. Sarihusada CSR program becomes accelerator of the community empowerment process. (2) Communicative action in the community empowerment process is characterized by interaction based on the awareness and willingness to communicate empathically and ethically.